Review: Antimicrobial properties of apis mellifera’s bee venom - El-Seedi, Hesham; Abd El-Wahed, Aida; Yosri, Nermeen; Musharraf, Syed Ghulam; Chen, Lei; Moustafa, Moustafa; Zou, Xiaobo; Al-Mousawi, Saleh; Guo, Zhiming; Khatib, Alfi; Khalifa, Shaden (MDPI, 2020)
Bee venom (BV) is a rich source of secondary metabolites from honeybees (Apis mellifera L.). It contains a variety of bioactive ingredients including peptides, proteins, enzymes, and volatile metabolites. The compounds contribute to the venom’s observed biological functions as per its anti-inflammatory and anticancer effects. The antimicrobial action of BV has been shown in vitro and in vivo experiments against bacteria, viruses, and fungi. The synergistic therapeutic interactions of BV with antibiotics has been reported. The synergistic effect contributes to a decrease in the loading and maintenance dosage, a decrease in the side effects of chemotherapy, and a decrease in drug resistance. To our knowledge, there have been no reviews on the impact of BV and its antimicrobial constituents thus far. The purpose of this review is to address the antimicrobial properties of BV and its compounds.